Louder and Faster Pain, Joy, and the Body Politic in Asian American Taiko - Wong, Deborah (University of California Press, 2019)
Louder and Faster is a study of taiko in California, focused on the play of sound, performance, identity, ethnicity, race, gender, and politics. Wong explores taiko as a music/dance art form that creates spaces in which memories of the WW2 Japanese American incarceration, Asian American identity, and a desire to be seen/heard intersect with global capitalism, the complications of mediation, and legacies of imperialism. Based on two decades of participatory ethnographic work, the book offers a vivid glimpse of an Asian American presence both loud and fragile.